PELATIHAN BAHASA INGGRIS PARIWISATA DI KAWASAN DESTINASI WISATA PANTAI, KECAMATAN PANGKALAN SUSU, KABUPATEN LANGKAT - Abdul Kadir Ritonga; Booni Tauhid; Tina Taviani (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The advancement of a tourist destination area must be supported by the level of quality and insight of Human Resources, namely insight into tourism activities, ability and skills to communicate and understand tourism with foreign tourists and domestic tourists. Based on the consideration of the potential for coastal tourism destinations as tourism areas, this community service program is designed to improve the competence of human resources, especially the management community with a focus on English for tourism competence. The objectives of this community service are (1) to help partners in service activities for community to solve problems related to tourism development and English for Tourism language skills, (2) to prepare tourism human resources who have English language competence, (3) to improve partnership relationships between institutions. The  results of  service activities for community that have been achieved consist of (a) tourism insight and community participation, (b) tourism English for Tourism language skills regarding coastal tourist destinations. Outcomes consist of an English for Tourism language tourism initiative, and the ability to converse in terms of explaining culinary variety, location maps and the natural beauty of coastal tourist destinations.